The phenomenon “spirituality” and language educat (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2018)
The article deals with the phenomenon “spirituality” as a basis of human existence, morality represented by the human pursuit of truth, love, tolerance, and respect for others. It is pointed out the need for the close interrelation of this phenomenon with education and Ukrainian language training as well. Definitions made by leading psychologists are given. They interpret spirituality as a valuable formation which characterizes the essence of the human as an active participant of global civilization. The Ukrainian teaching and learning support materials in the context of this philosophical and linguodidactic category are analyzed. The importance of key and subject competences for language education is pointed out. Methodical recommendations for university professors, language teachers based on the understanding of the signs of spirituality, their manifestation in the behavior of spiritually enriched language personality are given. The emphasis is made on the biblical texts that are appropriate to use during the Ukrainian language teaching. It is proved that all signs of spiritual personality, without exception, can be formed through the use of the Bible. This helps to penetrate into the world of words, closely study the verbal fabric of this Great Book. In the Bible, idioms represent a significant layer and their information involves cultural and connotative meaning. The application of evangelic verses, phrasemes of biblical origin which contain idioms, contributing to the understanding of the significance of spiritual factors for personality development is shown.
Keywords: phenomenon “spirituality”; biblical texts; language education; spiritual personality; key and subject competences